Facile preparation of a tetraethylenepentamine-functionalized nano magnetic composite material and its adsorption mechanism to anions: competition or cooperation. Issue 19 (16th March 2018) - Hu, Meiqin; Shen, Haoyu; Ye, Si; Wang, Yan; Zhang, Jiali; Lv, Shanshan
Abstract : A tetraethylenepentamine (TEPA)-functionalized nano-Fe3 O4 magnetic composite material (nFe3 O4 @TEPA) was synthesized by a facile one-pot solvothermal method. Abstract : A tetraethylenepentamine (TEPA)-functionalized nano-Fe3 O4 magnetic composite material (nFe3 O4 @TEPA) was synthesized by a facile one-pot solvothermal method. It was characterized by elementary analysis (EA), powder X-ray diffraction (XRD), Fourier transform infrared spectrometry (FTIR), transmission electron microscopy (TEM) and vibrating sample magnetometry (VSM). The results show that the nFe3 O4 @TEPA has an average size of ∼20 nm, with a saturation magnetization intensity of 48.2 emu g −1 . Its adsorption properties were investigated by adsorbing fluorine ions, phosphate, Cr(vi ) and their co-existing water system. The adsorption performance was studied as a function of solution pH, initial concentration of ions, contact time and temperature for each ion. The adsorption of the multi-ion co-existing system was studied via batch tests, XPS and FTIR analyses. The effect of co-existing ions was studied through Box-Behnken Design (BBD) and response surface methodology (RSM). It can be deducted that the adsorption mechanism of an individual fluorine ion or phosphate was mainly related to electrostatic attraction, while that of Cr(vi ) might be mainly related to electrostatic attraction and coordination interactions. For the fluorine ion and phosphate bi-component system, their adsorption was competitive via ion exchange. For the Cr(vi ), fluorine ion and phosphate tri-component co-existing system, Cr(vi ) took priority for adsorption and could replace the absorbed fluorine ion or phosphate by competitive reaction, but not vice versa .